Transient Localized Rotating Structures in a Suspension of Highly Thermophilic Nanoparticles - Carpineti, Marina; Castellini, Stefano; Pogliani, Andrea; Vailati, Alberto (Frontiers in Physics, 2022)
A thermophilic suspension of nanoparticles heated from below exhibits a complex stability diagram determined by the competition between the stabilizing flux of nanoparticles induced by thermophoresis and the destabilizing flux determined by thermal convection. We investigate Rayleigh-Bénard convection in a suspension of highly thermophilic nanoparticles with large negative separation ratio heated from below. We show that transient localized states appear in the range of Rayleigh numbers 2200